2016
DOI: 10.1039/c5dt03482e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivity with oxygen of Pr2NiO4+δ: an in situ synchrotron X-ray powder diffraction study

Abstract: The promising SOFC cathode material Pr2NiO(4.22) has been studied in situ under a pure oxygen atmosphere from 25 to 950 °C by high resolution synchrotron X-ray powder diffraction. At room temperature (RT) δ = 0.22(1), the average crystal structure turns out to be monoclinic. The subtle monoclinic distortion (γ = 90.066(1)° at RT), retained up to 460 °C, is interpreted in terms of specific tilt schemes of the NiO6 octahedra. It is also shown that Pr2NiO(4.22) is incommensurately structurally modulated already a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 42 publications
7
25
0
Order By: Relevance
“…In general, the refined details for Pr-rich F2/m structures in this study match well with results recently reported for Pr2NiO4+δ by Broux et al. 46 As discussed in that work, it is not realistic that the large refined anisotropic atomic displacement values for apical O(1) and equatorial O(2/3) oxygen sites imply significant thermal motion of these ions in the structure -which should be relatively small at 300 K -but more likely represent disordered or incommensurate ion displacements, such as octahedra tilting and/or steric repulsions from the interstitial oxygen site. Several previous reports on LNO and PNO have proposed structural models with split apical oxygen sites, 31,39,41 however it was recently shown by pair distribution function (PDF) analysis of neutron and X-ray powder that ambient temperature disorder of apical oxygen atoms in La2NiO4.18 can be well modeled by anisotropic atomic displacement parameters.…”
Section: Monoclinic Pr-rich Region (10 < X ≤ 20)supporting
confidence: 92%
See 3 more Smart Citations
“…In general, the refined details for Pr-rich F2/m structures in this study match well with results recently reported for Pr2NiO4+δ by Broux et al. 46 As discussed in that work, it is not realistic that the large refined anisotropic atomic displacement values for apical O(1) and equatorial O(2/3) oxygen sites imply significant thermal motion of these ions in the structure -which should be relatively small at 300 K -but more likely represent disordered or incommensurate ion displacements, such as octahedra tilting and/or steric repulsions from the interstitial oxygen site. Several previous reports on LNO and PNO have proposed structural models with split apical oxygen sites, 31,39,41 however it was recently shown by pair distribution function (PDF) analysis of neutron and X-ray powder that ambient temperature disorder of apical oxygen atoms in La2NiO4.18 can be well modeled by anisotropic atomic displacement parameters.…”
Section: Monoclinic Pr-rich Region (10 < X ≤ 20)supporting
confidence: 92%
“…The data for the Pr2NiO4+δ end member with δ ≈ 0.25 are well fit by a monoclinic F2/m space group with lattice parameters of a ≈ 5.39 Å, b ≈ 5.46 Å, c ≈ 12.45 Å, and γ ≈ 90.07° (see Table 1). This unit cell corresponds extremely well with details of the low temperature monoclinic (LTM) structure for Pr2NiO4+δ recently published in a separate investigation by Broux et al, 46 and provides confirming experimental evidence for an ambient temperature monoclinic structural distortion of Pr2NiO4+δ first proposed decades ago. 20,34,35 We note that close inspection by monochromatic labbased Cu Kα1 powder X-ray measurements of PNO also suggests a non-orthorhombic distortion, although less distinctly visible than in the HR-SPD datasets.…”
Section: Monoclinic Pr-rich Region (10 < X ≤ 20)supporting
confidence: 89%
See 2 more Smart Citations
“…14, 15 The phase transition from orthorhombic to HTT involves a small change in lattice parameters. Both a and b are within 0.06 Å in the orthorhombic structure 10 and equal in the HTT phase.…”
Section: Resultsmentioning
confidence: 99%